CITY TEXT OF WORKS OF T. SHEVCHENKO AS PREPOTENT ASPECT OF DISCLOSURE OF THE CITY TOPOS - Боклах, Д. Ю. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Aspects of functioning of the city text in works by T. Shevchenko are investigated in article. Features of allocation of the city topos are found out in texts. Characteristic signs of civilization and natural attributes in semiosis of the city text are defined.